A new modified tandem appliance for management of developing Class III malocclusion - Ram Sukh; Gyan P Singh; Pradeep Tandon (Wolters Kluwer Medknow Publications, 2013)
Most developing Class III patients display a retruded maxilla. Early intervention in mixed dentition is associated with better patient compliance and possibly a better orthopedic response, which can produce favorable results. The aim of this article is to present the fabrication of the new modified tandem appliance and its use in management of developing Class III malocclusion. The therapeutic results of a new modified tandem appliance are presented in an 8 year-old male patient with anterior cross bite and retrognathic maxilla at the mixed dentition stage. Anterior cross bite was corrected in 3 months and the positive overjet of 4 mm after continued use of the appliance for 1 year. There was a significant improvement in profile of the patient. The use of this appliance in this type of malocclusion enabled the correction of malocclusion in a few months and encouraging favorable skeletal growth in the future.